Producing the ‘problem of drugs’: A cross national-comparison of ‘recovery’ discourse in two Australian and British reports - Lancaster, Kari; Duke, Karen; Ritter, Alison (The International journal of drug policy, 2015)
•We examine how the problem of drugs was constituted in two reports on ‘recovery’.•The problem of drugs was represented as ‘dependence’ alone in both documents.•People who use drugs were constructed as either ‘responsibilised’ or ‘patientised’.•Conditional citizenship is reinforced in both documents.•The perceived authority of the UKDPC and ANCD was critical to the recovery debates. The notion of ‘recovery’ as an overarching approach to drug policy remains controversial. This cross-national analysis considers how the problem of drugs was constructed and represented in two key reports on the place of ‘recovery’ in drug policy, critically examining how the problem of drugs (and the people who use them) are constituted in recovery discourse, and how these problematisations are shaped and disseminated. Bacchi's poststructuralist approach is applied to two documents (one in Britain and one in Australia) to analyse how the ‘problem of drugs’ and the people who use them are constituted: as problematic users, constraining alternative understandings of the shifting nature of drug use; as responsibilised individuals (in Britain) and as patients (in Australia); as worthy of citizenship in the context of treatment and recovery, silencing the assumption of unworthiness and the loss of rights for those who continue to use drugs in ‘problematic’ ways. The position of the organisations which produced the reports is considered, with the authority of both organisations resting on their status as independent, apolitical bodies providing ‘evidence-based’ advice. There is a need to carefully weigh up the desirable and undesirable political effects of these constructions. The meaning of ‘recovery’ and how it could be realised in policy and practice is still being negotiated. By comparatively analysing how the problem of drugs was produced in ‘recovery’ discourse in two jurisdictions, at two specific points in the policy debate, we are reminded that ways of thinking about ‘problems’ reflect specific contexts, and how we are invoked to think about policy responses will be dependent upon these conditions. As ‘recovery’ continues to evolve, opening up spaces to discuss its contested meanings and effects will be an ongoing endeavour.